Assembly of tin oxide/graphene nanosheets into 3D hierarchical frameworks for high-performance lithium storage - Huang, Yanshan; Wu, Dongqing; Han, Sheng; Li, Shuang; Xiao, Li; Zhang, Fan; Feng, Xinliang (Chemsuschem, 2013)
3D hierarchical tin oxide/graphene frameworks (SnO2/GFs) were built up by the in situ synthesis of 2D SnO2/graphene nanosheets followed by hydrothermal assembly. These SnO2/GFs exhibited a 3D hierarchical porous architecture with mesopores (≈3 nm), macropores (3-6 μm), and a large surface area (244 m2 g-1), which not only effectively prevented the agglomeration of SnO2 nanoparticles, but also facilitated fast ion and electron transport in 3D pathways. As a consequence, the SnO2/GFs exhibited a high capacity of 830 mAh g -1 for up to 70 charge-discharge cycles at 100 mA g-1. Even at a high current density of 500 mA g-1, a reversible capacity of 621 mAh g-1 could be maintained for SnO2/GFs with excellent cycling stability. Such performance is superior to that of previously reported SnO2/graphene and other SnO2/carbon composites with similar weight contents of SnO2. Go go graphene electrodes! A strategy to fabricate monolithic three-dimensional (3D) graphene frameworks with SnO2 nanoparticles (SnO2/GFs) is presented. The combination of mesopores, macropores, large surface area, and 3D architecture of the hybrids not only effectively prevents agglomeration of SnO2 nanoparticles, but also facilitates fast ion and electron transport in 3D pathways, which results in an outstanding lithium storage performance. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrochemistry; graphene; mesoporous materials; nanoparticles; tin